The improved soil base model for the calculation of the combined raft pile foundation with the structural nonlinear behavior of the elements (Academic journal Industrial Machine Building Civil Engineering, 2023)
The paper considers and theoretically justifies the improved model of the soil base for the combined raft pile foundation (CRPF) to consider the nonlinear behavior of the elements “after” and “before” the connection between the raft and the piles (structural nonlinearity) to calculate the stress-strain state using the finite element method in present-day calculation packages. Using the improved model makes it possible to qualitatively simulate the behavior of the CRPF with the structural nonlinearity in the behavior of its elements. The simulation and numerical calculation of the base-CRPF system was performed using a specific example and it was found that the application of the proposed model with consideration to the structural nonlinearity of the behavior of the foundation elements reduces the moment forces in the raft to 15% in comparison with the application of the full load at once and the behavior of the raft with the permanent connection between the raft and the piles
Keywords: soil base; model; combined raft pile foundation; methodology; stress-strain state